Pengaruh Senam Jantung Sehat Terhadap Tekanan Darah Penderita Hipertensi - Novita Elisabeth Daeli (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Blood pressure is the pulse of the circulatory system that moves blood throughout the body. One physical and mental health is healthy cardio exercise which is beneficial for the health of the heart, brain, lungs, body and mind. The main goal of healthy cardio training is to strengthen the heart muscle, improve heart function, and increase oxygen flow throughout the body. Univariate analysis in the form of distribution of frequencies and proportions as well as bivariate analysis using the Wilcoxon test. The results of the study show that adult respondents 22 persons (50%), male 2 persons (5.5%), blood pressure before exercise (130-139 and/or 85-89 mmHg) up to 33 respondents (75%), blood pressure after exercise (<130-139 and/or 85-89 mmHg) 27 respondents (61,%). The results of the Wilcoxon test showed that cardio exercise had an effect on reducing blood pressure with p-values ??of 0.001 (<0.05). Based on the results, it is suggested that respondents do regular heart-healthy exercises to reduce high blood pressure.